Effects of soybean oil components on the microbial diversity of koji and flavor of Cantonese-style soy sauce - LI Xuewei, ZHU Xingui, ZHU Yayuan, ZENG Xiaobo (Zhongguo niangzao, 2025)
The intrinsic relationship between soybean oil components (SOC) and the flavor formation of Cantonese-style soy sauce was studied from microbial community structure and the flavor of soy sauce by constructing a soy sauce brewing model using soybean oil components with defatted soybeans. The results showed that the bacterial and fungal community structures in koji of soy sauce brewed with SOC was similar to those of traditional Cantonese-style soy sauce, significantly different from those of the koji of soy sauce brewed without SOC, and the richness was higher than that of koji of soy sauce brewed without SOC. The content of amino acids (6.38 g/100 ml) in the soy sauce brewed with SOC was the highest, the types of organic acids were rich and the content was relatively high, and the content of 16 major ester substances was the highest, aligning with type characteristic flavor profile of Cantonese-style soy sauce. The results demonstrated that the soybean oil components in the fermentation matrix positively regulated the unique microbial communities in Cantonese-style soy sauce production. Furthermore, most soybean oil components participated in the biotransformation of flavor compounds during Cantonese-style soy sauce brewing.